Immaterialism, Objects and Social Theory - Campbell, Norah (My University, 2019)
The philosopher Graham Harman argues that contemporary debates about the nature of reality as such, and about the nature of objects in particular, can be meaningfully applied to social theory and practice. With Immaterialism, he has recently provided a case-based demonstration of how this could happen. But social theorists have compelling reasons to oppose object-oriented social theory’s 15 principles. Fidelity to Harman’s aesthetic foundationalism, and his particular use of serial endosymbiosis theory as a mechanism of social change, constrain the very practices which it is supposed to enable. However, social theory stands to benefit from object oriented philosophy through what we call posthuman relationism – characterised as a commitment to the reality of the nonhuman, but not divorced from the human. The emphasis in object-oriented social theory on how objects withdraw from cognitive or affective capture and representation needs to be tempered by an equal focus on how objects appeal.
PUBLISHED
Keywords: Graham Harman; Object-oriented social theory; Posthuman relationism; Symbiosis; Digital Humanities; Identities in Transformation